Reducing eating disorder symptoms and risk factors using the internet: A meta‐analytic review. Issue 1 (26th November 2015) - Melioli, Tiffany; Bauer, Stephanie; Franko, Debra L.; Moessner, Markus; Ozer, Fikret; Chabrol, Henri; Rodgers, Rachel F.
ABSTRACT: Objective: The purpose of this meta‐analytic review was, first, to evaluate the efficacy of Internet‐based programs in decreasing eating disorder (ED) symptoms, and, second, to identify moderator variables these effects. Method: Twenty studies were identified and between‐group effect sizes were calculated for ED symptoms and risk factors. Results: Compared with control conditions, Internet‐based programs successfully decreased body dissatisfaction ( d = 0.28, 95% CI [0.15–0.41], p < .001), internalization of the thin ideal ( d = 0.36, 95% CI [0.07–0.65], p < .05), shape and weight concern ( d = 0.42, 95% CI [0.13–0.71], p < .05), dietary restriction ( d = 0.36, 95% CI [0.23–0.49], p < .001), drive for thinness ( d = 0.47, 95% CI [0.33–0.60], p < .001), bulimic symptoms ( d = 0.31, 95% CI [0.20–0.41], p < .001), purging frequency ( d = 0.30, 95% CI [0.02–0.57], p < .05), and negative affect ( d = 0.32, 95% CI [0.12–0.52], p < .001). Moderator analyses revealed no impact of data analytic strategy on intervention effects. Similarly, participant risk status was not a moderator for most outcomes. Discussion: Internet‐based programs are successful in decreasing ED symptoms and risk factors with small to moderate between‐group effect sizes.